Traditional Foods and Farming Models are Valuable for Tribal Farmers Health and Nutrition Security - Bhardwaj, Raju; Vyas, Latika; Parashar , Aabha (Epistemik Press, 2025)
The food ingredient composition of tribals have been changed from organically grown nutrient affluent millets, pulses, underutilized fruits and vegetables to chemically grown less nutritious rice, wheat, hybrid maize, potatoes, modern fruits and vegetables with residual loads of agro-chemicals. The physical working efficiency and health significance of tribal youths were continually deteriorating and they have lost interest in adopting agriculture as occupation and resulted in a significant increase in migration from original habitation to nearby towns or cities. The social reputation of farming and animal production occupation was also reduced among tribal youths due to harsh work environment, well-being of farmers and socio-economic revaluation in tribal areas. For exploring the changes in dietary composition, working efficiency, and interest in agricultural activities of the tribals, a comprehensive analysis of 85 studies available from literature and for factual validity of the results also conducted a wide-ranging field survey of tribal dominated areas. The maximum tribal farmers were found to be physically weakened, had lower immune systems, severely malnourished along with multiple nutrient deficiency disorders due to poor dietary intake because of ignorance of their traditional diets. This critical review emphasises the importance of balanced and adequate nutrition, popularization of traditional food products, adopting organic and traditional farming models for farmers good health and well being. Raising their physical work efficiency and also mental state for adopting agricultural occupation, reduce migration, improve socio-economic status and social reputation among tribal farmers.